Analisis peran guru dalam pembelajaran menulis aksara jawa di sekolah dasar - Esti Kaeksi; Joko Daryanto; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2023)
The purpose of this study was to describe the teacher's role in learning to write Javanese script at Elementary School. This is qualitative descriptive research using a case study approach. The results of this study show several roles have been carried out by the teacher, even though her roles as organizer and mediator/facilitator still do not fulfill each indicator, but the teacher's role as a demonstrator and evaluator in this study seems to be the most appropriate among the other teacher roles when viewed from the respective indicators for each role. As a demonstrator, the teacher has given examples of writing Javanese script on the whiteboard, both in terms of the shape and position/location of each letter and how to write it. Even though the teacher still doesn't master Javanese script material, the method used is in the form of lectures, and the teacher doesn't know the principles of learning the Javanese script. From the 3 indicators, the teacher fulfills 1 by being used as a demonstrator. As an organizer, all indicators have not been fulfilled by the teacher. The classroom atmosphere for learning is not conducive, the teacher cannot focus the attention of students; the teacher sometimes leaves the class due to various other activities so that students have the opportunity to be noisy and play in class when learning activities are still ongoing; and learning is still centered on the teacher. As a mediator and facilitator, the four indicators have not been fulfilled. Teachers have not created interactive learning and don’t facilitate students' learning through both learning resources and learning media. Then, as an evaluator, the teacher has provided an assessment after the learning activities are over through the students' cognitive learning outcomes. Even though the assessment process during the learning activities has not been carried out, one indicator has been fulfilled.